Artificial Intelligence-Enabled QR Codes in Nutrition Labelling: A Conceptual Paper. - MARIAPPAN, PRIYA KOLAPPALUR; MEENAKSHI; GURAPPA, PUSHPALATHA (Current Research in Nutrition & Food Science, 2025)
This conceptual paper explores the integration of artificial intelligence (AI) and quick response (QR) codes into nutrition labeling systems to address consumer concerns about food nutrition and the limitations of traditional labels. It highlights how AI-enabled QR codes can provide personalized, real-time nutritional information, offering an interactive and tailored consumer experience. The study emphasizes the potential of these technologies to improve accessibility, accuracy, and relevance of information, promoting healthier dietary behaviors. It also discusses challenges such as data privacy and user acceptance while underscoring the transformative potential of AI and QR codes in creating a more health-conscious and informed society.